2009
DOI: 10.1128/aac.01483-08
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole Antagonizes Virulence and Inflammation in Salmonella enterica -Infected RAW264.7 Cells

Abstract: The proton pump inhibitor omeprazole reduced the intracellular replication of Salmonella enterica serovar Typhimurium in RAW264.7 cells without affecting bacterial growth in vitro or the viability of the host cells. The mechanism was bacteriostatic and interfered with replication mediated by the virulence-associated SPI2 type III secretion system. The proton pump inhibitor bafilomycin A 1 , in contrast, mediated killing of intracellular bacteria and imposed a marked cytotoxicity on RAW264.7 cells. The two comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 44 publications
(54 reference statements)
5
23
0
Order By: Relevance
“…The salicylidene acylhydrazide INP0010 and the benzimidazole omeprazole block SPI2-assisted replication of S. Typhimurium in macrophage-like RAW264.7 cells [14,17]. Hence, a first purpose of this report was to define to what extent INP0010 and omeprazole exert combined effects on the intracellular replication of S. Typhimurium.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The salicylidene acylhydrazide INP0010 and the benzimidazole omeprazole block SPI2-assisted replication of S. Typhimurium in macrophage-like RAW264.7 cells [14,17]. Hence, a first purpose of this report was to define to what extent INP0010 and omeprazole exert combined effects on the intracellular replication of S. Typhimurium.…”
Section: Introductionmentioning
confidence: 96%
“…Amongst such compounds are the salicylidene acylhydrazides [12][13][14] and the thiazolidinones [10,15] that affect T3SS activity in several species of Gram-negative pathogens. The macrolide bafilomycin as well as the benzimidazole omeprazole also affect SPI2-associated virulence traits [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…21 Another recent publication describes that the proton pump inhibitor omeprazole blocks T3S in S. enterica. 22 The salicylidene acylhydrazides (Fig. 1), are promising since they target T3S in Yersinia pseudotuberculosis, Shigella flexneri, enterohemorrhagic E. coli, and Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…As TrxA was needed for SPI2 activity in vitro, we set out to analyze to what extent the functionality of SPI2 was affected by TrxA during infection of macrophage-like RAW264.7 or epithelial MDCK cells. We have previously shown that SPI2 genes are already induced in macrophage-like and epithelial cells at 4 h postinfection (16,24) and that SPI2-mediated intracellular replication is not manifested before 8 h postinfection in our settings of cell culture infections (44). Thus, in order to avoid any effects related to bacterial intracellular replication while enabling the recording of significant numbers of intracellular bacteria, we infected RAW264.7 or MDCK cells with wild-type or TrxA-deficient S. serovar Typhimurium carrying plasmid p2777 at an MOI of 100:1 and limited the infection to an 8 h period of time.…”
Section: Spi2mentioning
confidence: 99%